Nosocomial infections in the departments of orthopedics and traumatology - Maksimović Jadranka M.; Marković-Denić Ljiljana N.; Bumbaširević Marko; Marinković Jelena M. (Vojnosanitetski Pregled)
Aim. To determine the incidence and the localization of nosocomial infections (NI) in the departments of orthopedics and traumatology. Methods. A prospective cohort study carried out between February 1 and July 31, 2002 included all of the surgical patients who were hospitalized longer than 48 hours, as well as 30 days after the discharge. The patients were examined and their diagnoses made according to the definition of NI, that was based on the clinical and/or laboratory findings. Results. Out of 277 hospitalized patients, 78 had a total of 91 NIs. Sixty seven (85.8%) of the patients had 1 registered NI each, 9 (11.6%) of the patient had 2 NIs each, while only the 2 (2.6%) were with 3 NIs. The incidence of the patients with HAI was 28.2% (95% IP = 22.9-33.5), while the incidence of HAI was 32.8%. The patients who developed a NI were hospitalized almost twice as long as the patients who did not (t test = 6.0, DF = 275, p < 0.001). In regard to the duration of hospitalization, the incidence of NI was 12.3 per 1000 patient-hospital days. The patients operated on most frequently had the surgical-site infections (69.2%). Of 63 infections of the surgical site, 3 patients (4.8%) were diagnosed as having the NI at that localization following the discharge, and then the urinary tract infections, 25.3% (23/91), and sepsis, 5.5% (5/91). Conclusion. Epidemiological surveillance was the first step towards the prevention and the eradication of NI. The results of this study could be of use in planning of the adequate measures for the prevention of NI in the departments of orthopedic surgery.